The Communicative Approach in Arabic Language Learning (Theoretical and Practical Perspectives) - Isop Syafei; Ade Arip Ardiansyah; Dadan Nugraha (Gunung Djati Conference Series, 2025)
This study explores the communicative approach in Arabic language learning from both theoretical and practical perspectives as a response to the need for functional and contextual language proficiency. In the context of modern education, Arabic language learning can no longer rely solely on grammatical mastery; instead, it must be directed toward the ability to communicate effectively in various real-life situations. The purpose of this study is to examine the communicative approach in Arabic language teaching from both theoretical and practical aspects. A qualitative approach was employed, using library research and limited field observation in Arabic teaching practices. Data were collected through documentation, field notes, and analysis of learning materials, and then analyzed descriptively and critically. The findings show that the communicative approach theoretically emphasizes the use of Arabic in real-life contexts, based on language acquisition theory and communicative competence. Practically, it requires interactive methods, teacher training, contextual materials, and digital technologies to enhance students’ language skills, motivation, and understanding of religious and social values in an integrated manner. These findings affirm that the communicative approach should be systematically integrated into the Arabic language curriculum and instructional strategies to make learning more relevant, effective, and meaningful.